Analysis of increasing public participation in electoral politics in Sidoarjo district in 2024 - Mulyaningsih, Mulyaningsih; Widiastuti, Ika (International Journal on Social Science, Economics and Art, 2024)
The problem that occurs is that community participation in politics has not increased regarding general elections in Sidoarjo Regency. The aim of the research is to find out how community participation in general elections in Sidoarjo Regency can increase. The research method uses descriptive qualitative. Data collection techniques were carried out using observation, interviews and documentation methods. The results of the research are that the implementation of community political participation in the 2024 general elections in Sidoarjo Regency has experienced quite a high increase.